IgA ANTI-DENGUE PROFILE IN SAMPLES WITH POSITIVE DENGUE PCR OR NS1 - M Thohirin Ramadhani; Aryati Aryati; M Vitanata Arfijanto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Dengue Virus Infection (DVI) causes several clinical manifestations and requires varied diagnostic instruments. IgA anti-dengue as one of the diagnostic markers of DVI is suspected to have a shorter lifespan and greater sensitivity in detecting secondary infections compared to IgM anti-dengue. This study was conducted using 34 sera with positive RT-PCR or NS1 dengue virus. Samples were examined by a reverse flowimmunochromatographic method using AIM Dengue IgA Assure Rapid Test and will be analyzed its profile toward the day of fever, serotype, severity, platelet count, and type of infection. The overall sensitivity of IgA anti-dengue was 61.76% (n=34); in which IgA anti-dengue detected 14.29% primary and 66.67% secondary cases. IgA anti-dengue detected DEN1, DEN2, DEN3, and Mixed DEN1 – DEN3 virus serotype respectively 55.56%, 22.22%, 16.67%, and 5.56% (n=20). The day of fever was dominated by day-4 and day-5 respectively 28.57% (n=21). IgA anti-dengue was detected in DD, DHF grade I, II, and III 42,86%, 28.57%, 19.05%, and 9.52% (n=21) respectively. IgA anti-dengue detected in all levels of platelet count, it detected 60% in < 50,000 cell/mm3, 30% in 50,000 - 100.000 cell/mm3 and 10% in > 100,000 cell/mm3 platelet count sample (n=20). In conclusion, IgA anti-dengue showed a good performance, applicable as a diagnostic marker of DVI.